2018
DOI: 10.1002/gcc.22524
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic implications of TNFAIP3/A20 deletions in extranodal NK/T‐cell lymphoma

Abstract: The A20/Tumor necrosis factor-alpha-induced protein 3 (A20/TNFAIP3) is a negative regulator of NF-κB signaling. We analyzed the clinicopathologic implications of A20 deletions in extranodal NK/T-cell lymphoma (NKTL). Fluorescence in situ hybridization analysis of the A20 gene was performed using archived formalin-fixed tissues in 49 cases of NKTL. Among the 49 NKTL patients (median age, 48 y [10-79]), stage I-II (75% [36/48]) and upper aerodigestive tract (UAT)-origin (84% [41/49]) were predominant. All A20 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…The intracellular ubiquitin editing protein tumor necrosis factor alpha-induced protein 3 (TNFAIP3), also known as A20, negatively regulates the activity of NF-κB in a variety of pathways through tumor necrosis factor and Toll-like receptors [12][13][14]. The TNFAIP3 gene locus is located in chromosome band 6q23, and its deletion frequently occurs in B-cell lymphomas, particularly extranodal marginal zone B cell lymphoma and diffuse large B-cell lymphoma [15][16][17]. Additionally, a few previous studies have revealed that TNFAIP3 deletion is frequently found in cutaneous T-cell lymphoma (CTCL) and NK-T cell lymphoma (NKTCL) [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular ubiquitin editing protein tumor necrosis factor alpha-induced protein 3 (TNFAIP3), also known as A20, negatively regulates the activity of NF-κB in a variety of pathways through tumor necrosis factor and Toll-like receptors [12][13][14]. The TNFAIP3 gene locus is located in chromosome band 6q23, and its deletion frequently occurs in B-cell lymphomas, particularly extranodal marginal zone B cell lymphoma and diffuse large B-cell lymphoma [15][16][17]. Additionally, a few previous studies have revealed that TNFAIP3 deletion is frequently found in cutaneous T-cell lymphoma (CTCL) and NK-T cell lymphoma (NKTCL) [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The TNFAIP3 gene locus is located in chromosome band 6q23, and its deletion frequently occurs in B-cell lymphomas, particularly extranodal marginal zone B cell lymphoma and diffuse large B-cell lymphoma [15][16][17]. Additionally, a few previous studies have revealed that TNFAIP3 deletion is frequently found in cutaneous T-cell lymphoma (CTCL) and NK-T cell lymphoma (NKTCL) [15,18,19]. Moreover, the prognostic value of TNFAIP3 deletion in NKTCL patients has been investigated, but the results are contradictory [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Classical Hodgkin lymphoma (cHL), a subtype of HL accounting for 95% cases, is characterized by the presence of less than 1% malignant mononucleated Hodgkin and multinucleated Reed-Sternberg cells (HRS cells) mixed with nonneoplastic cells [ 175 ]. NF-κB signaling pathway, which is regulated by A20 and CYLD, is very important for the survival and proliferation of HRS cells [ 176 ].…”
Section: Introductionmentioning
confidence: 99%
“…A20 mutations and/or deletions are linked with various subtypes of B-cell or T-cell lymphomas, including mucosal-associated lymphoid tissue (MALT) lymphoma, DLBCL, MCL, FL and NKTL [ 208 210 ]. In NKTL, monoallelic deletion of A20 occurs in 18% cases, while no biallelic deletion was detected [ 175 ]. A20 mutations occur in more than 50% of ABC-DLBCL and a small fraction of GCB-DLBCL [ 211 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation